2003
DOI: 10.1213/01.ane.0000048088.17761.b4
|View full text |Cite
|
Sign up to set email alerts
|

A Single Small Dose of Postoperative Ketamine Provides Rapid and Sustained Improvement in Morphine Analgesia in the Presence of Morphine-Resistant Pain

Abstract: A small-dose ketamine and morphine regimen interrupted severe postoperative pain that was not relieved previously by morphine. Ketamine reduced morphine consumption and provided rapid and sustained improvement in morphine analgesia and in subjective feelings of well-being, without unacceptable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
3
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 28 publications
(32 reference statements)
8
95
3
6
Order By: Relevance
“…The use of low doses of ketamine is associated with a lower incidence of adverse effects and is widely accepted by patients [19]. Therefore, analgesic protocols with fewer adverse effects than those found with the use of opioids should be evaluated [2].…”
Section: Discussionmentioning
confidence: 99%
“…The use of low doses of ketamine is associated with a lower incidence of adverse effects and is widely accepted by patients [19]. Therefore, analgesic protocols with fewer adverse effects than those found with the use of opioids should be evaluated [2].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, dextroketamine is widely used as analgesic therapy adjuvant in humans, in spite of the lack of studies confirming its effectiveness and of discussions with regard to its routine clinical use. Some authors have shown that low dextroketamine doses associated to morphine potentiate analgesia and decrease opioids adverse effects, as well as its ability to decrease pain scores 9 . A large prospective study has shown safety of intravenous dextroketamine and morphine for patient--controlled analgesia 10 .…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study examined tolerant patients in the recovery room and revealed the beneficial effect of a simple postoperative ketamine bolus to limit acute tolerance to postoperative morphine. 24 Dextromethorphan has similar properties as ketamine, but has been much less studied. Besides ketamine, clonidine and dexmedetomidine have been studied.…”
Section: Intraoperative Periodmentioning
confidence: 99%
“…7 Une étude récente s'est penchée sur des patients tolérants en salle de réveil, et a révélé l'intérêt d'un simple bolus postopératoire de kétamine pour limiter la tolérance aiguë à la morphine en postopératoire. 24 Le dextrométorphan présente les mêmes propriétés que la kétamine mais a été beaucoup moins étudié. Outre la kétamine, la clonidine et la dexmedétomi-dine ont fait l'objet d'études.…”
Section: Période Peropératoireunclassified